1121. Epidemiology and Risks for Infection Following Cytoreductive Surgery and Hyperthermic Intra-Peritoneal Chemotherapy at an Australian Centre. (26th November 2018) - Smibert, Olivia; Slavin, Monica; Thursky, Karin; Teh, Ben; Penno, Janelle; Ismail, Hilmy; Worth, Leon
Abstract: Background: Cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (CRS-HIPEC) is associated with improved cancer survival but increased risk of infection in patients with abdominal-pelvic malignancy. We evaluated risks and characteristics of infectious outcomes at an Australian cancer centre. Methods: Patients undergoing CRS-HIPEC between January 2016 and November 2017 at Peter MacCallum Cancer Centre were retrospectively reviewed. Malignancy type, comorbidities, perioperative risk factors, and infectious complications were captured, using standardized definitions for surgical site infection. Association between risk factors and infection outcomes was evaluated by logistic regression modeling. Results: Sixty-nine patients underwent CRS-HIPEC, predominantly for colorectal cancer and pseudomyxoma peritonei. Overall, 32 (46.3%) experienced an infectious complication, including infections at surgical site (16), respiratory tract (6), urinary tract (5), Clostridium difficile (2), and post-operative sepsis (10). In most, infection onset was within 7 days post-operatively. Median length of hospitalisation was 20 days for patients with infection, compared with 8 days for those without ( P = 0.000). Of variables potentially associated with infection at surgical site, small bowel resection (OR 5.56, 95% confidence interval [CI] 1.09–28.19; P = 0.039) and number of resected viscera (OR 1.71, 95% CI 1.05–2.76; P = 0.029) were significantly associated with infection on univariate analysis. Conclusion: We demonstrate a significant burden of early infective complications in patients undergoing CRS-HIPEC, including surgical and non-surgical site infections. Findings support the need for multimodal programs to reduce the risk of a broad range of infections in this population. Higher risk subgroups, including those with small bowel resection and increased number of resected viscera, may benefit from enhanced monitoring. Disclosures: All authors: No reported disclosures.